Performance Analysis of a Desiccant Evaporative Cooling System for Mango Fruit Storage in the Savannah and Transitional Zones of Ghana (Agricultural Engineering, 2019)
Performance analysis of a 1.0 tonne desiccant evaporative cooling storage structure for mango fruits was studied. The study examined the effects of inlet air conditions and water flow rates through an absorber on the cooling performance of the system. The airflow rate was approximately 0.24 m3·s−1 and water flow rates through the absorber varied from 0 to 0.252 l·s−1. The system produced approximately 7 kW of cooling at water supply rate of 0.252 l·s−1. A simple linear correlation was established for condition line slope from inlet to exiting air conditions for all the water flow rates. Lines of best fit resulted in correlation coefficient better than 0.96. The observed temperatures with a direct evaporative cooler, tested with freshly harvested mango fruits were found to be between 15.1°C and 23.4°C and relative humidity between 81.8% and 97.7%. Physiological weight loss and firmness assessments of the fruits were also conducted.